Variation in the Evolution and Sequences of Proglucagon and the Receptors for Proglucagon-Derived Peptides in Mammals - Irwin, David M. (Frontiers in Endocrinology, 2021)
The mammalian proglucagon gene (Gcg) encodes three glucagon like sequences, glucagon, glucagon-like peptide-1 (GLP-1), and glucagon-like peptide-2 that are of similar length and share sequence similarity, with these hormones having specific cell surface receptors, glucagon receptor (Gcgr), GLP-1 receptor (Glp1r), and GLP-2 receptor (Glp2r), respectively. Gcgr, Glp1r, and Glp2r are all class B G-protein coupled receptors (GPCRs). Despite their sequence and structural similarity, analyses of sequences from rodents have found differences in patterns of sequence conservation and evolution. To determine whether these were rodent-specific traits or general features of these receptor genes in mammals I have analyzed the gene and protein sequences for proglucagon and the receptors for proglucagon-derived peptides from the genomes of 168 mammalian species. Single copy genes for each gene were found in almost all genomes. In addition to glucagon sequences within Hystricognath rodents (e.g., guinea pig), glucagon sequences from a few other groups (e.g., pangolins and some bats) as well as changes in the proteolytic processing of GLP-1 in some bats are suggested to have functional effects. GLP-2 sequences display increased variability but accepted few substitutions that are predicted to have functional consequences. In parallel, Glp2r sequences display the most rapid protein sequence evolution, and show greater variability in amino acids at sites involved in ligand binding, however most were not predicted to have a functional consequence. These results suggest that Glp2r might be more promiscuous in its binding to ligands than Gcgr or Glp1r.